The puzzle of money laundering: a literature review of regulations and implications - Anjani, Arina; Widiastuti, Harjanti (Journal of Accounting and Investment, 2024)
Research aims: This study intends to investigate how Anti-money laundering (AML) regulations work and assess their effectiveness on a global level. Additionally, it also consigns to explain how technology has been adopted to prevent and treat money laundering.Design/Methodology/Approach: This study employed a systematic literature review method. The data, encompassing 63 reviewed articles, were derived from the Scopus database. This research underwent three phases: extraction, analysis, and synthesis process.Research findings: Archival emerged as the predominant method applied in the reviewed articles. These articles significantly impacted the effectiveness of AML regulations and the preparedness of all entities to put them into practice. However, in addition to the positive effects of AML, there existed adverse effects and risks. Accordingly, the utilization of technology could lessen negative impacts.Theoretical contribution/Originality: Notwithstanding the significance of worldwide AML regulations, there existed a lack of literary research on compliance and technological trends. The findings of this study are expected to impact policymakers, practitioners, and the public on the enhancements to the AML system and the augmentation of global security.Practitioner/Policy implication: Banks and other financial institutions implemented AML to prevent money laundering.Research limitation/Implication: This study focused solely on the effectiveness of AML, compliance with AML regulations, challenges, and the application of technology in AML.